Revisiting the social and religious value of humour - Cloete, Anita (Stellenbosch Theological Journal, 2019)
The aim of the article is to revisit and reintroduce the social and religious significance of humour. The chapter will examine humour as a complex human action by focusing on the function thereof in everyday life. The discussion will be informed by examples of the value of humour for physical and mental health, politics and religion. Politics and religion serve among the most popular themes and sources for comedy today, especially in stand-up comedy. These examples will illustrate how humour enables people (individuals and communities) to cope with life by engaging them in an open-ended process in which alternative perspectives and attitudes become possible. As a cultural and contextual human action, humour can also serve as social commentary on social challenges and, by doing so, raise social awareness about burning issues in society. Moreover, the discussion will especially highlight two aspects of humour, namely tension and paradox. It will argue that embracing humour as a hopeful attitude that unlocks alternative perspectives of viewing reality needs more attention, especially from a religious perspective. The final section will, therefore, consider the religious significance of humour by expounding on the relationship with faith and hope.